THE OLD CHURCH SLAVONIC FLORILEGIUM OF BULGARIAN TSAR SIMEON IN A NEWLY IDENTIFIED MANUSCRIPT COPY FROM THE GRAND DUCHY OF LITHUANIA (in Russian) - TEMČIN, SERGEJ (Knygotyra, 2015)
The author introduces a previously unknown East Slavic manuscript copy of the Florilegium translated from Greek into Old Church Slavonic upon the initiative of the Bulgarian tsar Simeon (893–927). This newly identified copy is present in a miscellany (Moscow, Russian State Archive of Early Acts, F. Mazurin’s collection (f. 196), inventory 1, Nr. 616)) written in the third quarter of the 16th century in the Ruthenian lands of the Grand Duchy of Lithuania (GDL), but after 1656 removed to be carried abroad (tentatively, in Moscow). The Tsar Simeon’s Florilegium is known solely from its later manuscript copies written by East Slavic and Serbian scribes. The earliest manuscript was carefully written and richly decorated in 1073 for Sviatoslav Yaroslavich, the Grand Prince of Kiev (1073–1076) and is now known as Sviatoslav’s Izbornik or the Izbornik of 1073. Currently, 3 Serbian and 28 East Slavic manuscript copies (full or partial), written prior to the 19th century, are known. At least 10 of the East Slavic copies belong to the Cyrillic manuscript tradition of the GDL. Some of them are not merely valuable but also provide unique textual evidence, as is the copy contained in the manuscript No 5/1082 in the collection of the Kirillo-Belozersk monastery, now kept in the Russian National Library in St Petersburg: the manuscript contains one of the two known copies of the Laudatio to the Tsar Simeon and is the only one which preserves his name (since in the other copy of 1073 his name had been erased and replaced with the name of Sviatoslav, for whom the manuscript was created). The author demonstrates that the above mentioned manuscript, which is now kept at the Russian State Archive of Early Acts in Moscow, should actually be recognized as another one, previously unknown, copy of the Tsar Simeon’s Florilegium. The same manuscript also contains a unique copy of the Cyrillic manual of Hebrew – an interesting written monument of Christian East Orthodox and Jewish cultural collaboration which took place probably in Kiev in the second half of the 15th century. All the texts chosen from a full copy of the Tsar Simeon’s Florilegium to be included in this manuscript are identified by the author and indicated in the article. Their list contains almost 170 entries which form nearly 40% of the total number in the Florilegium. The newly identified manuscript copy additionally highlights the significance of the Cyrillic written tradition of the GDL in preserving the Tsar Simeon’s Florilegium and in disseminating its text in the East Slavic milieu during the Middle Ages.